ADMINISTRATIVE DATA PROCESSING SYSTEM RENTAL MACHINES ON UD. JAYA MOLEN USING MICROSOFT VISUAL BASIC 6.0 - Joni Iskandar; Drs Sunarto Usna. Skom. MMSi (Jurnal Sistem Informasi, 2003)
Information technology has become a part share of economic activity and business.This technology is believed to bring positive impact to the start of the reason forefficient use of time and accuracy of data. So, no wonder if all the competingeconomic activities using information technology as a means penigkatan satisfactionof the needs. No exception to the revenue administration is the business sector intrade (from UD) Molen emerging Jaya.Along with the need to further simplify the data processing in data processingmachines for the administration of lease rentals, we need a data processing system toreplace the system of computerized data processing is done manually. Hence madethe processing and administration system using a machine rental program newapplications for data collection engine leasing process easier in data processing andinformation needs of customers, machines and rentals can be achieved easily andaccurately.The author hopes that with the existence of administrative data management systemrental machine that writers make, hopefully it will be useful for the needy.